2021
DOI: 10.1080/21655979.2021.1988361
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of N-terminal pro-B-type natriuretic peptide (NT-pro BNP) combined with D-dimer for no-reflow phenomenon in patients with acute coronary syndrome after emergency of percutaneous coronary intervention

Abstract: Acute coronary syndrome (ACS) is a critical illness in cardiovascular disease. The purpose of this study was to investigate the value of N-terminal pro-B-type natriuretic peptide (NT-pro BNP) and D-dimer in predicting the occurrence of no reflow in emergency percutaneous coronary intervention (PCI) in patients with ACS. 168 ACS patients were recruited, including 88 patients with normal reflow and 80 patients with no reflow after emergency of PCI. The levels of serum NT-pro BNP and D-dimer in the patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In ACS patients with STsegment elevation myocardial infarction (STEMI), the increase in NT-proBNP levels is attributable to acute myocardial infarction, which induces the release of NT-proBNP from the Short Communication ventricles due to elevated stress on the left ventricular wall [15][16][17][18]. NT-proBNP levels can also be used to assess silent myocardial ischemia [19,20]. NT-proBNP is also associated with the regulation of various physiological functions that control energy metabolism, myocardial ischemia, and the development of organ damage, including left ventricular hypertrophy and peripheral artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…In ACS patients with STsegment elevation myocardial infarction (STEMI), the increase in NT-proBNP levels is attributable to acute myocardial infarction, which induces the release of NT-proBNP from the Short Communication ventricles due to elevated stress on the left ventricular wall [15][16][17][18]. NT-proBNP levels can also be used to assess silent myocardial ischemia [19,20]. NT-proBNP is also associated with the regulation of various physiological functions that control energy metabolism, myocardial ischemia, and the development of organ damage, including left ventricular hypertrophy and peripheral artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…This study also found that NT-pro-BNP levels were higher in the no-reflow group than in the reflow group. The findings in this study indicate that preoperative levels of NT-pro-BNP in combination with D-dimer can also be used as predictive biomarkers for the incidence of no-reflow after PCI [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 The neurohormone N terminal pro-B-type natriuretic peptide (NT-proBNP), which is elevated in acute myocardial infarction and angina pectoris, is synthesized and released by ventricular muscles. 3 The two basic sources of BNP and NT-proBNP release are wall stress and myocyte stretch. Among its various activities are sympathetic nerve activation, natriuresis, vasodilation, and inhibition of the renin-angiotensin-aldosterone system.…”
Section: Introductionmentioning
confidence: 99%